Single-nucleus RNA sequencing reveals ARHGAP28 expression of podocytes as a biomarker in human diabetic nephropathy - Zhang Fengxia; Tang Xianhu; Zeng Zhimei; Cao Chunyu; Yun Caocui; Shen Yue; Nie Chaohong; Xiong Ying; Chulian Mao; Wu Yueheng; Xu Ruiquan (Open Medicine)
Diabetic kidney disease (DKD) represents serious diabetes-associated complications, and podocyte loss is an important histologic sign of DKD. The cellular and molecular profiles of podocytes in DKD have yet to be fully elucidated.